Correlation between Sestrin-2 and PERK Signaling in Matured Porcine Oocytes according to ER-stress during In Vitro Maturation - Hyo-Jin Park; In-Su Kim; Jin-Woo Kim; Seul-Gi Yang; Min-Ji Kim; Deog-Bon Koo (The Korean Society of Animal Reproduction and Biotechnology, 2019)
Sestrin-2 (SESN2) as a stress-metabolic protein is known for its anti-oxidative effects as a downstream factor of PERK pathways in mammalian cells. However, the expression patterns of SESN2 in conjunction with the UPR signaling against to ER stress on porcine oocyte maturation in vitro, have not been reported. Therefore, we confirmed the expression pattern of SESN2 protein, for which to examine the relationship between PERK signaling and SESN2 in porcine oocyte during IVM. We investigated the SESN2 expression patterns using Western blot analysis in denuded oocytes (DOs), cumulus cells (CCs), and cumulus-oocyte complexes (COCs) at 22 and 44 h of IVM. As expected, the SESN2 protein level significantly increased (p < 0.01) in porcine COCs during 44 h of IVM. We investigated the meiotic maturation after applying ER stress inhibitor in various concentration (50, 100 and 200 μM) of tauroursodeoxycholic acid (TUDCA). We confirmed significant increase (p < 0.05) of meiotic maturation rate in TUDCA 200 μM treated COCs for 44 h of IVM. Finally, we confirmed the protein level of SESN2 and meiotic maturation via regulating ER-stress by only tunicamycin (Tm), only TUDCA, and Tm + TUDCA treatment in porcine COCs. As a result, treatment of the TUDCA following Tm pre-treatment reduced SESN2 protein level in porcine COCs. In addition, SESN2 protein level significantly reduced in only TUDCA treated porcine COCs. Our results suggest that the SESN2 expression is related to the stress mediator response to ER stress through the PERK signaling pathways in porcine oocyte maturation.